Importance of Learning Terminology in Being Aware of Profession - Axmatovich, Elchayev Zohidjon (Researchparks Publishing, 2023)
In acquisition of any language, terminology is considered to be the fundamental knowledge in obtaining micro linguistic skills such reading, writing, speaking and listening. In ESP classes, vocabulary or technical terminology is main knowledge to understand the specialty in English. technical terminology gives us a full concept of profession and its branches. A learner can be aware of meaning of terminology of the field of study only by reading written contexts. This paper highlights the ways of learning terminology in two languages.